1997
DOI: 10.1139/f97-114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH, calcium, alkalinity, hardness, and chlorophyll on the survival, growth, and reproductive success of zebra mussel (Dreissena polymorpha) in Ontario lakes

Abstract: In 1991, field studies were conducted to determine the effects of pH, calcium, alkalinity, hardness, and chlorophyll on the survival, growth, and reproduction of zebra mussel (Dreissena polymorpha). Water from 16 south-central lakes in Ontario was collected and supplied to zebra mussels in a flow-through system. Adult zebra mussel mortality was significantly correlated with calcium and pH. Growth rates of juvenile mussels ranged from -83.3 to 200 µm ·week-1. Water buffer variables (calcium, alkalinity, and tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 20 publications
3
53
0
Order By: Relevance
“…The importance of these parameters has been confirmed and further refined by statistical analyses of the observed occurrence of zebra mussel populations in Europe (Ramcharan et al 1992a(Ramcharan et al , 1992b, and North America (Hincks and Mackie 1997).…”
mentioning
confidence: 80%
“…The importance of these parameters has been confirmed and further refined by statistical analyses of the observed occurrence of zebra mussel populations in Europe (Ramcharan et al 1992a(Ramcharan et al , 1992b, and North America (Hincks and Mackie 1997).…”
mentioning
confidence: 80%
“…Jones & Ricciardi (2005) found that zebra mussel biomass in the St. Lawrence River increased linearly with increasing calcium concentrations below 15 mg/l, peaked between 23 and 25 mg/l and decreased thereafter. Negative effect of high calcium levels was observed by Hincks & Mackie (1997), who found that adult mortality increased above 25 mg/l and maximum juvenile growth rates decreased above 32 mg/l. In laboratory tests, Sprung (1987) found that when exposed to different calcium concentrations, rearing success and larval condition of zebra mussel were roughly constant for concentrations from about 35 to 106 mg/l.…”
Section: Phmentioning
confidence: 95%
“…In North America, however, zebra mussels have been reported as present and sometimes abundant at calcium levels ranging from 12 to 25 mg/l (Cohen & Weinstein 2001). Laboratory studies found the minimum calcium threshold for normal development and long-term survival of zebra mussels to range from 8.5 to 12 mg/l (Sprung, 1987, Vinogradov et al, 1993, Hincks& Mackie, 1997. Based on field studies, some authors reported no zebra mussels below 15 mg/l (Mellina & Rasmussen 1994, Strayer et al, 1996, and others suggested a threshold for occurrence between 8 and 10 mg/l (Jones & Ricciardi, 2005).…”
Section: Phmentioning
confidence: 99%
“…In a previous study 8 where juveniles of Margaritifera margaritifera were cultured from four rivers, it was found that water temperature, dissolved oxygen, conductivity, pH, ammonia, nitrite, nitrate, phosphorus, sodium, potassium, magnesium, and calcium had correlation to growth. Moreover, it was found that pH, alkalinity, total hardness and calcium had a significant relationship to the survival and growth rate of zebra mussel (Dreissena polymorpha) adults 37 .…”
Section: Water Qualitymentioning
confidence: 99%